Pengaruh Debt default, Mandatory disclosure, dan Ukuran Perusahaan Terhadap Opini Audit Going Concern - Sintania Geanita; Budi Kurniawan (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2022)
This research examines the effect of debt default, mandatory disclosure, and company size on going concern audit opinion. The population in this study are all manufacturing sector companies listed on the Indonesia Stock Exchange (IDX) in 2016-2019. The number of samples used in this study were 68 companies with a sampling technique using purposive sampling and the number of observations of research data obtained was 272. The research method used was logistic regression. The results of the study conclude that debt default has a positive effect on going-concern audit opinion. Mandatory disclosure has a negative effect on going-concern audit opinion, while firm size has no effect on going-concern audit opinion.